POLA HARMONI SOSIAL MASYARAKAT MATARAMAN DI KOTA KEDIRI - Taufik Alamin (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2021)
Since the days of the kingdom, the Kediri area has been inhabited by people from various ethnic groups, languages, religions, and beliefs. It also includes many places of worship such as mosques, churches, pagodas, temples, studios and Islamic boarding schools. The existence of these places of worship not only shows the level of plurality and tolerance of its citizens, this process also occurs over a long period of time. This study aims to reveal more deeply about the model of social integration carried out by the people of Kediri in the midst of dynamics and changes that continue to occur.This research was conducted using a qualitative method, using a case study approach in Kediri. Data was collected by using observation and interview methods and using relevant document sources. From these data, analysis and interpretation of the selected data is then carried out, to then draw a conclusion. Furthermore, the writing and construction of research results are carried out.The results of this study indicate that social integration in the Kediri community has been created in three forms of community social life, namely in the fields of slametan rituals, traditional arts and inter-religious relations. The three forms turned out to be able to become a binder for other social systems, even bridging interactions between actors and uniting them in a shared social system. The social integration model used in building social harmony is the proceduralist model and the assimilationist model.